Interfacial Morphology Addresses Performance of Perovskite Solar Cells Based on Composite Hole Transporting Materials of Functionalized Reduced Graphene Oxide and P3HT. Issue 5 (13th March 2018) - Gatti, Teresa; Lamberti, Francesco; Topolovsek, Peter; Abdu‐Aguye, Mustapha; Sorrentino, Roberto; Perino, Luca; Salerno, Marco; Girardi, Leonardo; Marega, Carla; Rizzi, Gian Andrea; Loi, Maria Antonietta; Petrozza, Annamaria; et al.
Abstract : The development of novel hole transporting materials (HTMs) for perovskite solar cells (PSCs) that can enhance device's reproducibility is a largely pursued goal, even to the detriment of a very high efficiency, since it paves the way to an effective industrialization of this technology. In this work, we study the covalent functionalization of reduced graphene oxide (RGO) flakes with different organic functional groups with the aim of increasing the stability and homogeneity of their dispersion within a poly(3‐hexylthiophene) (P3HT) HTM. The selected functional groups are indeed those recalling the two characteristic moieties present in P3HT, i.e., the thienyl and alkyl residues. After preparation and characterization of a number of functionalized RGO@P3HT blends, we test the two containing the highest percentage of dispersed RGO as HTMs in PSCs and compare their performance with that of pristine P3HT and of the standard Spiro‐OMeTAD HTM. Results reveal the big influence of the morphology adopted by the single RGO flakes contained in the composite HTM in driving the final device performance and allow to distinguish one of these blends as a promising material for the fabrication of highly reproducible PSCs. Abstract : The conformation adopted by single reduced graphene oxide flakes dispersed in a P3HT matrix is determined by the type of organic substituents grafted covalently to their surface. When these composite materials are employed as hole‐transporting materials in perovskite solar cells, their morphology determines the performance: with the smooth ones providing reproducible devices with good power conversion efficiency (PCE), while the crumpled ones generating undesired local short circuits that ultimately reduce PCE.